Penggunaan Alat Peraga Sate Bilangan Untuk Meningkatkan Hasil Belajar Matematika Di Sekolah Dasar - Layli Widya Hasanah; Karlina Wong Lieung; Fredy; Wa Ode Siti Hamsinah Day; Sri Hanipah (Yayasan Perguruan Kampus, 2024)
The main problem in learning mathematics in elementary schools is the weak learning process caused by ineffective teaching methods, teachers tend to use conventional approaches that make it difficult for students to understand the material, resulting in low student learning outcomes. In this context, numeracy skills, including addition, subtraction, multiplication and division, are very important because they are closely related to daily activities. This study aims to improve the learning outcomes of mathematics multiplication material by using Numbers Satay Props for class II students of Wasur 2 Merauke State Elementary School in the 2022/2023 academic year, totaling 20 students. The design of this class action research includes: 1) planning 2) implementation 3) observation 4) reflection. This research took place in two cycles, each cycle had three meetings. The data collection methods in this study are: 1) test 2) observation 3) documentation. The results of this study indicate that the use of Numbers skewers media improves the learning process of math multiplication material. This is evidenced by the increase in student learning outcomes in counting. In the pre-cycle the number of students who completed as many as 11 students (55%). In cycle I the number of students who completed as many as 15 students (75%). In cycle II the number of students who were complete was 20 students (100%).